The Factors that Influence Saving Behaviour of Student at State Polytechnic of Sriwijaya - Ahmad Hafiz Wijanarko; Sulastri Sulastri; Kemas Husni Thamrin (Budapest International Research and Critics University, 2022)
Good financial condition is certainly the desire of every human being to be able to live in prosperity. To achieve these conditions, of course, good financial management is needed from each individual. This study aims to analyze the factors that influence saving behaviour in Sriwijaya State Polytechnic students. The sampling technique used to determine the sample in this study is the purposive sampling technique. The data that was processed came from 140 students of the Sriwijaya State Polytechnic which was obtained from a questionnaire that was distributed directly. Furthermore, the data were analyzed using Partial Least Square - Structural Equation Model (PLS-SEM). The results show that financial literacy does not affect saving behaviour, materialism affects saving behaviour and financial literacy and materialism mediated by impulse buying affect saving behaviour. Thus, further research is expected to add other factors that are not included in this study, such as the income of parents, peers, or family financial education.